Management of Industrial Relations Mediator Training at the Employment Human Resource Development Center - Irma Della Puspita Safrani; Desi Rahmawati; Dimas Kurnia Robby (Asosiasi Asesmen Pendidikan (AAP), 2026)
This study aims to analyze the planning, implementation and evaluation related to the training of industrial relations mediators batch 98 at the Center for Manpower Human Resource Development. This study uses a descriptive method with a qualitative approach. Data collection techniques include observation, documentation studies, and interviews. Data validity check techniques include credibility, transferability, dependability, and confirmability tests. Data analysis techniques include data reduction, data presentation, conclusion drawing and data verification. The results of this study show that the planning stage starts from the analysis of training needs, the preparation of programs and curriculum, and the determination of widyaiswara. The implementation stage includes online and offline learning, assignments and exams, then the final seminar of the training. The evaluation stage starts from making training evaluation instruments including participant evaluation, widyaiswara, training implementation, coaches, mentors, testers, after all data is collected, the evaluation field makes a report on the training results